New Results for Some Intuitionistic Fuzzy Partial Functional Differential Equations with State-Dependent Delay - Bouchra Ben Amma; Said Melliani; Lalla Saadia Chadli (Sahand Communications in Mathematical Analysis)
In this research work, we investigate novel findings concerning the existence and uniqueness of intuitionistic fuzzy solutions for state-dependent delay intuitionistic fuzzy partial functional differential equations with local initial conditions in a new weighted intuitionistic fuzzy complete metric space under suitable assumptions. The main results of this paper are based on the Banach fixed point theorem. An illustrated example of our results is given with some numerical simulations for $β$-cuts of the intuitionistic fuzzy solutions.